2017
DOI: 10.15421/011729
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the structural indices of annual shoots of Quercus rubra under anthropogenic impact

Abstract: Air pollution is one of the important problems of large cities. In connection with this, comprehensive study of the mechanisms of the corresponding reactions of tree species, introduced in the process of landscaping, to various environmental factors is required. The aim of this study is to analyze the influence of urban technogenic environmental pollution on the anatomical characteristics of Quercus rubra Linnaeus, 1753 annual shoots. The object of research was 35-year-old plants of Q. rubra, which grew in a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…The previous research showed that moderate doses of toxic substances stimulate the thickening of cork parenchyma more intensively in R. centifolia and R. rugosa, whereas severe contamination inhibits the development of this tissue. Bessonova and Kryvoruchko (2017) showed that in the shoots of Quercus rubra L. plants growing in roadside plantation, there was an increase of the cork and collenchyma thickness indices, 4 radial rows of cells in the reference area, 6 rows in the test area, which according to the authors, ensures better protection of internal tissues from the penetration of pollutants.…”
Section: The State Of the Anatomical Indices Of Robinia Pseudoacacia mentioning
confidence: 92%
“…The previous research showed that moderate doses of toxic substances stimulate the thickening of cork parenchyma more intensively in R. centifolia and R. rugosa, whereas severe contamination inhibits the development of this tissue. Bessonova and Kryvoruchko (2017) showed that in the shoots of Quercus rubra L. plants growing in roadside plantation, there was an increase of the cork and collenchyma thickness indices, 4 radial rows of cells in the reference area, 6 rows in the test area, which according to the authors, ensures better protection of internal tissues from the penetration of pollutants.…”
Section: The State Of the Anatomical Indices Of Robinia Pseudoacacia mentioning
confidence: 92%
“…Саме тому використання розповсюджених видiв урбанофлори в бiоiндикацiї дозволяє оцiнювати рiвень забруднення промислових агломерацiй. Аналiз наукової лiтератури свiдчить, що iндикаторними видами техногенного забруднення можуть слугувати сiльськогосподарськi культури [10,16,26]; деревнi рослини [5,7,22,28]; трав'янистi види [5,14,33].…”
unclassified